Digital Communication in Libraries to Promote Inclusive Societies: A Systematic Literature Review (Universitas Terbuka, 2025)
This study systematically reviews studies published between 2019 and 2025 on the role of digital communication in libraries in promoting an inclusive society. Using the PRISMA methodology as a guide, the analysis focuses on digital strategies, inclusivity, and governance. Findings indicate that academic libraries expanded off-campus digital access during the COVID-19 pandemic, while AI-based assistive technologies improved accessibility for users with disabilities. However, governance challenges—such as limited control over content curation and ethical issues in AI use—persist. Theoretically, digital communication functions as a mechanism for democratizing knowledge, providing broader access to information for non-elite audiences. Practically, libraries need to balance technological innovation with ethical governance, participatory curation, and inclusive policies to enhance social equity.